Anodyne Practice of Turning Composite Fuel into Green Energy at Mini Thermal Power Plants in India: A Case Study: Alternate source of energy using coal blended biomass (Indian Journal of Engineering and Materials Sciences (IJEMS), 2023)
The exploitation of non-renewable energy resources since last few decades has been a foremost concern for today’s generation. Most of the energy demand (about 63%) of India is outfitted by thermal power plants, leading to massive emission of CO2, thereafter, fly ash generation causing threat to eco-system. India being second largest producer of rice paddy globally also harvests large number of crops such as wheat, sugarcane, corn, etc. accreting substantial amount of biomass annually. In association with the current agenda for sustainable development, biomass (Rice Husk) co-firing with coal has been identified as most practicable solution for the energy generation in modern times particularly, for small scale power plants at rural sector.  The paper explains comparative economy in power generation with the help of three cases based on theoretical assumptions. Composite fuel with biomass: coal ratio of 80:20 and 90:10 predicts about 8-10% economy in energy generation related with pure coal-based power plants. The leftover from this process is termed as composite ash, utilization of which is essential for environmental safety. Being diverse in composition than coal fly ash (CFA), composite ash can be turned into sodium silicate, powdered silica and further Molecular Sieves.  All these products find commercial utility in chemical industries as an ion exchange, adsorbent, detergent-builder, abrasive, fertilizer, etc.